Optimizing Student Achievement with the Quantum Teaching Approach - Fauzan Fauzan; Artamin Hairit; Raden Ahmad Muhajir Ansori (Molang: Journal Islamic Education, 2024)
Learning activities are often faced with challenges that interfere with teachers and students in achieving educational goals, such as difficulties in providing effective feedback and improving student learning skills. This can result in learning difficulties for students due to the application of less applicable methods. Various teaching methods are needed in order to increase students' enthusiasm and motivation to learn. The Quantum Teaching method is believed to be able to create a pleasant learning environment by utilizing students' natural potential, including their curiosity. This method is implemented through the TANDUR stages: Grow, Experience, Name, Demonstrate, Repeat and Celebrate. This study uses a descriptive qualitative approach with a type of library research that refers to various sources to understand the use of the Quantum Teaching Method in classroom learning activities. The results show that this approach has great potential to improve the effectiveness of learning in the educational environment. This research shows that the Quantum Teaching Method is effective in improving student achievement which includes cognitive, affective, and psychomotor aspects. Cognitive aspects are improved through six levels of learning: knowledge, comprehension, application, analysis, synthesis, and evaluation. Affective aspects can be improved through five levels of activities: receiving, responding, valuing, organization, and characterization. Meanwhile, psychomotor aspects can be improved through seven activity steps: perception, set, guided response, mechanism, complex overt response, adaptation, and origination.